2006
DOI: 10.1016/j.jtcvs.2005.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for primary graft dysfunction after lung transplantation

Abstract: Our analysis of donor and recipient risk factors for severe primary graft dysfunction identified patient groups at high risk for poor outcomes after lung transplantation that might benefit from treatments aimed at reducing reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 20 publications
6
150
2
2
Order By: Relevance
“…In part, this is due to the high incidence (11-25%) of PGD, even in well-preserved ''ideal organs'' (23)(24)(25)(26). The use of the Pa O 2 /FI O 2 index, or P/F ratio, for assessing acute lung dysfunction from acute lung injury (index < 300) and adult respiratory distress syndrome (index < 200) is the accepted standard (27), and the use of the P/F ratio in assessing PGD has recently been established (23,28). In this study, we applied the P/F ratio as a measure of acute lung injury/ PGD and found a significant correlation of PGD with anti-col(V) immune status before transplantation, a novel finding with a number of important implications for lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is due to the high incidence (11-25%) of PGD, even in well-preserved ''ideal organs'' (23)(24)(25)(26). The use of the Pa O 2 /FI O 2 index, or P/F ratio, for assessing acute lung dysfunction from acute lung injury (index < 300) and adult respiratory distress syndrome (index < 200) is the accepted standard (27), and the use of the P/F ratio in assessing PGD has recently been established (23,28). In this study, we applied the P/F ratio as a measure of acute lung injury/ PGD and found a significant correlation of PGD with anti-col(V) immune status before transplantation, a novel finding with a number of important implications for lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are scored on this grading system at the time immediately posttransplant, and then at 24, 48, and 72 h posttransplant. Those who have PGD 3 persisting to the 72-h point have the worst short-and long-term outcomes (Whitson et al 2006).…”
Section: Postoperative Carementioning
confidence: 99%
“…Some studies 3 have suggested that only the diagnosis of pulmonary arterial hypertension itself increases the risk of PGD; other studies 29 suggest that each higher increment of pulmonary artery pressure (from any underlying lung disease) translates to an increase in risk of PGD. In addition, because patients with significant pulmonary hypertension require CPB to undergo the transplantation procedure, it is difficult to tease out the respective causal roles.…”
Section: Discussionmentioning
confidence: 99%